2018
DOI: 10.1208/s12249-018-1088-y
|View full text |Cite
|
Sign up to set email alerts
|

Development of Orodispersible Films Containing Benzydamine Hydrochloride Using a Modified Solvent Casting Method

Abstract: The aim of this study was to develop benzydamine hydrochloride-loaded orodispersible films using the modification of a solvent casting method. An innovative approach was developed when the drying process of a small-scale production was used based on a heated inert base for casting the film. During this process, two types of film-forming maltodextrins for rapid drug delivery were used. They were plasticized with two different polyols (xylitol and sorbitol). Superdisintegrant Kollidon® CL-F was tested as an exci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 41 publications
1
23
0
1
Order By: Relevance
“…The surface pH of ODFs is commonly investigated to ensure that the pH of the dosage form is in the range of physiological saliva (5.8–7.4). An ODF with a pH largely differing from this may cause local mucosal irritation and discomfort for the patient [39]. The ODFs prepared in this study all revealed a neutral pH (Table 5) indicating that no local side effects should be encountered at the administration site.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…The surface pH of ODFs is commonly investigated to ensure that the pH of the dosage form is in the range of physiological saliva (5.8–7.4). An ODF with a pH largely differing from this may cause local mucosal irritation and discomfort for the patient [39]. The ODFs prepared in this study all revealed a neutral pH (Table 5) indicating that no local side effects should be encountered at the administration site.…”
Section: Resultsmentioning
confidence: 95%
“…The printed formulations consisted of as few excipients as possible as a preference expressed by the medical doctors at HUS, however, disintegrants, saliva stimulating agents, sweeteners, taste masking agents, flavors, colorants, etc., may be introduced in the formulation to further tailor the properties of the ODF or to fulfill individual preferences of a patient. The amounts used of these types of ingredients are typically quite low in ODFs [37,38,39], and it is, therefore, unlikely that addition of these materials dramatically would change the printability nor the quality of the printed ODFs. As EXT and IJP nonetheless are techniques that require different properties of the formulation to be printable, the idea was to use the same HPC solution (15% w / w ) as a substrate for IJP which subsequently was imprinted with a drug ink and which in the case of EXT was drug-loaded and printed into ODFs in a single step.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the thickness of wet strip cast, the rheological and physicochemical properties of the cast solution affect the drying speed. [83,84] These limit the scale-up process, which could affect the final thickness of the dried strip. Furthermore, the selection of solvents depends on the solubility of the API, its stability in the solvents and its heat sensitivity during the drying process.…”
Section: Solvent Castingmentioning
confidence: 99%
“…The surface pH of an ODF should preferably be as close to physiological saliva (5.8-7.4) as possible to ensure a comfortable mouthfeel. Local mucosal irritation and discomfort may occur with the administration of an ODF with pH outside this range [42]. UL and DL films without LP had a surface pH of 4.83 ± 0.15 and 4.63 ± 0.65 respectively, which is too acidic for an ODF and may cause discomfort upon administration.…”
Section: Surface Phmentioning
confidence: 99%